The Effect of Digital Learning Media Utilization and Learning Motivation on Learning Participation - Siti Asrofah; Sulastri Rini Rindrayani; Kadeni Kadeni (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2025)
This study aims to analyze the effects of digital learning media and learning motivation on students’ learning participation in the Science and Social Science (IPAS) subject at the elementary school level. The research used a quantitative approach with an associative design to examine the effect of two independent variables, namely the use of digital learning media (X₁) and learning motivation (X₂), on students’ learning participation (Y). The research sample consisted of 35 sixth-grade students from SD Negeri 1 Boyolangu, Tulungagung Regency, using a saturated sampling technique in which the entire population served as the research subjects. Data were collected through Likert-scale questionnaires to measure the intensity of digital learning media use and students’ learning motivation, along with documentation to support the data. The research instruments were tested for validity and reliability to ensure accurate measurement. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 26. The research results showed that the use of digital learning media and learning motivation significantly affected students’ learning participation. Learning motivation emerged as the most dominant variable, with a regression coefficient of 0.359 (p = 0.011), while digital learning media showed a coefficient of 0.286 (p = 0.018). An R2 value of 0.612 indicates that these two variables can explain 61.2% of the variation in students’ learning participation